2017
DOI: 10.1038/s41467-017-00712-3
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy between in-plane magnetic susceptibility and resistivity anisotropies in extremely strained BaFe2As2

Abstract: High-temperature superconductivity in the Fe-based materials emerges when the antiferromagnetism of the parent compounds is suppressed by either doping or pressure. Closely connected to the antiferromagnetic state are entangled orbital, lattice, and nematic degrees of freedom, and one of the major goals in this field has been to determine the hierarchy of these interactions. Here we present the direct measurements and the calculations of the in-plane uniform magnetic susceptibility anisotropy of BaFe2As2, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
51
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 60 publications
10
51
1
2
Order By: Relevance
“…Due to the absence of a magnetic order, a simple orbital-driven nematic order has been proposed to understand the nematic transition in FeSe [33]. In this case, a trivial SOC effect will be expected with a negligible in-plane anisotropy for spin susceptibility, which should be simply scaled with the orbital order [36,60]. Clearly, this is inconsistent with our observation.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Due to the absence of a magnetic order, a simple orbital-driven nematic order has been proposed to understand the nematic transition in FeSe [33]. In this case, a trivial SOC effect will be expected with a negligible in-plane anisotropy for spin susceptibility, which should be simply scaled with the orbital order [36,60]. Clearly, this is inconsistent with our observation.…”
Section: Discussioncontrasting
confidence: 90%
“…This case was verified by the RPA calculation in BaFe 2 As 2 by only considering a ferro-orbital order without invoking spin d.o.f. [36]. In this situation, the above conjecture is naturally satisfied.…”
Section: Evidence For Spin-space Anisotropy: Uniform Spin Susceptimentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, new piezo-based strain-tuning devices have been presented [7,8] and used in the study of ruthenates [9,10] and SmB 6 [11]. Additionally, strain has been famously employed to probe the nematic susceptibility of iron-based superconductors [12][13][14][15][16]. Applying strain means enforcing a deformation, or length change with respect to a 'free' reference state, and can be achieved using a rigid device.…”
mentioning
confidence: 99%
“…Previous studies on the ultrafast dynamics suggest that the component of τ ∼ 1 ps is common in Fe‐based materials with spin and/or orbital order at low temperature . The ultrafast dynamics in underdoped Ba(Fe,Co) 2 As 2 showed that a nematic signal of a relaxation time of a few tens of ps shows up below the structural phase‐transition temperature T S , whereas the fast one of τ ∼ 1 ps develops only below the magnetic phase‐transition temperature T N < T S .…”
mentioning
confidence: 93%